2019
DOI: 10.1002/adem.201900762
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐Mediated Anisotropic Lattice Expansion in Ceramics as Evidence for Nonthermal Coupling between Electromagnetic Fields and Matter

Abstract: Electromagnetic (EM) fields can trigger a range of surprising responses in materials. Microwave radiation (MWR), a type of EM field in the frequency range of 0.3–300 GHz, can lower the synthesis temperature required for ceramics such as TiO2 and induces mixed amorphous–crystalline phase compositions. To better understand the effects of MWR on matter, structural changes during microwave heating and MWR‐assisted synthesis using in situ synchrotron X‐ray diffraction are studied. Anisotropic expansion–contraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 82 publications
(93 reference statements)
2
17
0
Order By: Relevance
“…Experiments utilizing an identical experimental setup and heating conditions found that no phase formation occurs without MWR exposure, indicating that the chemical environment is not responsible for the observed effects. 43 Synthesis using an MWR absorbing SiC vial (in place of the standard borosilicate glass) shields the growth solution from EM eld exposure while maintaining similar heating rates, 44 and also results in no thin lm growth. 22 Additionally, thin lms synthesized at identical temperatures in a conventional furnace were found to have a completely disordered atomic structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments utilizing an identical experimental setup and heating conditions found that no phase formation occurs without MWR exposure, indicating that the chemical environment is not responsible for the observed effects. 43 Synthesis using an MWR absorbing SiC vial (in place of the standard borosilicate glass) shields the growth solution from EM eld exposure while maintaining similar heating rates, 44 and also results in no thin lm growth. 22 Additionally, thin lms synthesized at identical temperatures in a conventional furnace were found to have a completely disordered atomic structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S19 †) and prior experiments have demonstrated the success of MWRassisted synthesis on particles that are not electrically conducting. 43 This indicates that local EM eld absorption, regardless of the electrical properties of the absorber, can promote material growth. With this evidence, we have obtained new insight into how synthesis and phase transitions progress under EM excitation, demonstrating that local electric eld strengths are dependent on the applied power and can impact local atomic order without signicantly altering the crystalline atomic structure.…”
Section: Resultsmentioning
confidence: 99%
“…This aligns well with prior studies on EM eld-assisted methods, which have obtained evidence for oxygen defect-mediated reactions but were not able to characterize the local atomic structure. 7,9,17,69,70 Nanoparticle size effects may also inuence the local structure and contribute to changes in the interatomic distances in both MWR-assisted and conventionally synthesized SnO 2 . [71][72][73][74] The relationship between the size and structural disorder in MWR-assisted nanoparticles warrants further investigation.…”
Section: Phase Formation Mechanismsmentioning
confidence: 99%
“…3,4 Additionally, MWR has been shown to impact atomic structure and phase transitions in ways not observed without EM eld exposure. [5][6][7][8][9][10] These effects have made MWR-assisted synthesis an appealing option for a wide variety of material systems, 2 with applications in Li-ion batteries, 11,12 photovoltaics, 13,14 and catalysis. 15,16 However, the mechanisms underlying the role of EM elds in promoting phase formation and structural transitions remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…An example for the former is field-driven decrystallization of materials. 23,24,55,56 Bottom panel in Figure 3a shows an x-ray diffraction pattern, where the sharp peaks indicate crystalline anatase TiO 2 . 56 When exposed to time-varying microwave radiation at 2.45 GHz, peak intensity decreases drastically, indicating decrystallization.…”
Section: Fundamental Questions-atomistic Structural Changes Under Electric and Electromagnetic Fieldsmentioning
confidence: 99%